METODE BERMAIN AIR OUTDOOR DALAM MENGOPTIMALKAN FISIK MOTORIK HALUS ANAK USIA 4-5 TAHUN DI RA DARUL AMIN SEMPU - Lilis Nurul Habibah; Imam Wahyono (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2020)
Fine motoric physical maturity is important to support children's readiness in learning to read, write and count (calistung). Lack of attention to fine motor physical readiness makes the learning process (Calistung) complicated and difficult, leaving playing as a stimulation method very often occurs. So how do you use the outdoor water play method so that you can optimize the physical motor skills of children aged 4-5 years? This research was conducted at RA Darul Amin Sempu. This research is a descriptive qualitative research. The research data were collected through observation, documentation and interview methods. The data analysis technique used was the Miles and Huberman model, the validity of the data used source triangulation and method triangulation. The results showed the use of the outdoor water play method was carried out in 3 stages (preparation, implementation and evaluation), familiar outdoor activities carried out daily such as: washing, watering plants as well as water relay, making the implementation very frequent, both at school and at home, so that indirectly it makes fine motor physical stimulation occur repeatedly and results in optimal fine motor physical development, as shown by all study subjects who are able to achieve STPPA according to their age.